Analisis Yuridis Dihapusnya Ketentuan Pasal 26 Ayat (4) Undang-Undang No. 32 Tahun 2009 Tentang Perlindungan Dan Pengelolaan Lingkungan Hidup Dalam Undang-Undang No. 11 Tahun 2020 Tentang Cipta - Akhmad Munawar; Muhammad Aini; Dedi Sugiyanto; Miftah Ulumudin Tsani (Scholar Center, 2021)
The 1945 Constitution of the Republic of Indonesia Article 28 H paragraph (1) states that everyone has the right to live in physical and spiritual prosperity, to have a place to live, and to have a good and healthy living environment and have the right to obtain health services. After the enactment of the Employment Creation Law on October 5, 2020, the impact of changes to several provisions stipulated in the PPLH Law, including the part that was deleted was Article 26 paragraph (4) of the PPLH Law which reads